Does COVID-19 confinement period affect the body composition and physical performance of young elite soccer players? - de Paula Oliveira, L.; Aquino, R.; de Castro, F. M. P.; Pimenta, P. M.; Gonçalves, L. G. C.; Nobari, H.; Puggina, E. F. (Research Square, 2022)
Background: The current pandemic caused by COVID-19 generated several changes in lifestyle. However, with the gradual return of activities, there are divisions about the real impact of the confinement period on the body composition and the players' motor capacities. The objectives of the present study were to verify the effects of a COVID-19 confinement period on body composition and physical performance in young soccer players.